Efficacy of fungicides for controlling downy mildew of rapeseed - U.N. SAIKIA, K.C. PUZARI and (Indian Phytopathology, 2002)
The efficacy of 4 fungicides (metalaxyl (as Apron 35 WS), benomyl (as Benlate), captan (as Hexacap) and mancozeb + thiophanate-methyl (as Indofil M 45)) was tested using different methods of treatment against Peronospora parasitica infecting rape in Assam, India. Of these, seed treatment with metalaxyl at 6 g/kg seed and seed treatment with metalaxyl combined with 2 sprays of mancozeb + metalaxyl (as Ridomil MZ 72) at 0.2% were the most effective.